Symposium 4: Malta Networked Learning Forum 2021: Experiences and Reflections - Cutajar, Maria; De Laat, Maarten; Ryberg, Thomas (Proceedings of the International Conference on Networked Learning, 2024)
This symposium presents 3 papers relating to the Malta-based Networked Learning (NL) Forum 2021. The first two papers review the expectations and experiences of early researchers participating in the forum. The third paper presents reflections on the hybrid modality in which the forum convened. The purpose of this symposium and its component papers looking back on a NL community initiative is to look back, inform and look ahead to future similar events which potentially serve novice researchers develop connectedness to the broader networked learning community of scholars and peer researchers. In this symposium, we use the term ‘early researchers’ (ERs) rather than the prevalent early-career researchers (ECRs) to distinguish between the graduate and doctoral level researchers grouping which arose for the case of the NL Forum 2021 event from the overlapping doctoral and postdoctoral category to which the term ECRs more commonly refers to (McAlpine, Pyhältö, & Castelló, 2018).